Teaching Visually Impaired Students in Inclusive Classrooms at Early Childhood Level: Early Childhood Development Teachers’ Perceptions in the Context of Gilgit - Sadia Bano; Sadruddin Bahadur Qutoshi; Jalani, Ghulam (JIE, 2025)
The purpose of this study is to explore the teachers’ perceptions about teaching visually impaired students in inclusive classrooms and challenges they face at Early Childhood Development (ECD) level. This research was conducted at one of ECD schools in Gilgit Baltistan using a qualitative case study approach. Data was gathered through semi-structured interviews. The results revealed that teachers have basic understanding regarding inclusive education, its importance and the teaching strategies to teach in an inclusive setting (where all mainstream and visually impaired learners are given opportunity to learn). However, teachers still need to have more knowledge regarding inclusive education to better help visually impaired students. Shortage of special needs teachers, time limitations, rigid curriculum and crowded classes are some of the major challenges. It is recommended that teachers should be facilitated with an advanced level of training in the domain of inclusive education. Additionally, facilities such as enough classrooms full of required resources and special needs of teachers would be ensured to enable both mainstream learners and visually impaired students in inclusive ECD classes.